BOOK REVIEW: Sailing through the high waters of current public debates and politics of memory. Reflections on the new monograph published by Catherine Horel on the Horthy-era in the context of the current debates on the contemporary history of Hungary - TAMÁS, Lönhárt (Studia Universitatis Babeș-Bolyai Historia, 2020)
The “fall of the idols” of the Marxist-Leninist world view cleared the scene which had a referential role to public actors in a need for sources and means of symbolic legitimating. In the process of de-legitimating of the Communist system, an important role has been played by the hyphening of the scarcity of resources and the growing scale of poverty at the societal level, as the discourse on the eradication of poverty was of a referential value of the Communist political identity – of an ever-higher value for the János Kádár-led Hungarian regime. The issue of Hungarian minorities’ gradually worsening situation in the neighbouring states, as part of a generally growing referential value of the ethno-culturally defined national agenda, including national sovereignty and independence, in a state which remained attached to a Soviet Union oriented loyalty up to the late 1980’s, were part of a new, alternative set of referential values which played an important symbolic role also in legitimating regime change. The need for a new symbolic figure for “the father of the nation” with a referential role for an ever larger solidarity, challenging and uprooting the compromised solution-based Kádár regime’s symbolic hegemony (which tried to build up its symbolical reference to the era of long peace and welfare between 1867 and 1918, attached to the father figure of Franz Joseph), had let to a revival of the cult of historical personalities identified with nationalism, independence and sovereignty, motivated by political legitimating. In that struggle for symbolic reference, the political actors had tried several strategies which after all had not succeeded entirely neither to eradicate the symbolic capital of Kádár (as in the early 2000’s still had held an essential public presence as one of the most referential Hungarian figures of the 20th Century, with a strong nostalgic background for its economically based, socially appeasing policies), neither to build up a symbolic consensus around any other historical or public personality of the same century. Symptomatic for the current situation is that the main symbolic place of the capital city of Hungary is still a scenery of an ongoing “battle” of the politics of memory, which was gradually reshaped by restated statues of pre-20th century leaders, and also not assumed entirely by the public. The symbolic capital of leaders which marked the Hungarian 20th Century seems to be eroded by the ever-louder political fight for imposing each side’s hegemonic view on the other side’s responsibilities for the tragedies of the last century.